1986
DOI: 10.1242/dev.97.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Whisker growth induced by implantation of cultured vibrissa dermal papilla cells in the adult rat

Abstract: Retention of the capacity to induce the growth of hair by cultured adult rat vibrissa dermal papilla cells has been investigated. Small pellets of serially cultured papilla cells were implanted into the bases of the exposed follicular epidermis of amputated adult rat vibrissa follicles. Amputated follicles that received no cell implants or implants of cultured dorsal skin fibroblasts were used as controls. Over 50% of follicles implanted with cultured papilla cells in the passage range 1–3 grew hairs. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These aggregative microtissues are essential for HF formation, as they first initiate the signal for HF development and subsequently orchestrate with the overlying epithelium for HF morphogenesis. , Previous experiments have demonstrated that cultured rodent papillae have inductive potential. , Other studies indicated intact human DP exhibited hair-inductive capacity when recombined with bulge-derived epithelial cells . As a specialized cell population, DP cells are distinguishable from inter follicular dermal fibroblasts by their unique characteristics including self-aggregation, distinct gene and protein expression, and more importantly the hair-inductivity. ,, However, DP cells are inclined to lose these biological properties during in vitro expansion that have been observed and characterized before or around passage 8, suggesting that cells at such later passage (P8) not only lose the trichogenic ability but also likely undergo an aging process. Previous studies that either using conditioned medium , or adding defined proteins ,, have been described to maintain the inductive potential of cultured DP cells.…”
Section: Discussionmentioning
confidence: 99%
“…These aggregative microtissues are essential for HF formation, as they first initiate the signal for HF development and subsequently orchestrate with the overlying epithelium for HF morphogenesis. , Previous experiments have demonstrated that cultured rodent papillae have inductive potential. , Other studies indicated intact human DP exhibited hair-inductive capacity when recombined with bulge-derived epithelial cells . As a specialized cell population, DP cells are distinguishable from inter follicular dermal fibroblasts by their unique characteristics including self-aggregation, distinct gene and protein expression, and more importantly the hair-inductivity. ,, However, DP cells are inclined to lose these biological properties during in vitro expansion that have been observed and characterized before or around passage 8, suggesting that cells at such later passage (P8) not only lose the trichogenic ability but also likely undergo an aging process. Previous studies that either using conditioned medium , or adding defined proteins ,, have been described to maintain the inductive potential of cultured DP cells.…”
Section: Discussionmentioning
confidence: 99%
“…5,8,9 Dermal papilla cells isolated from rat and guinea pig vibrissae, as well as humans, could also induce HF formation when implanted into recipient nonhairy skin. 10,11 Basal keratinocytes also have the capacity to facilitate HF regeneration under induction. 12 Three core proteins, apolipoprotein A1, galectin 1, and lumican, are necessary to induce HF neogenesis from nonhair fibroblasts, via the activation of insulin-like growth factor and Wnt signaling.…”
Section: Intergender Hand Transplant: a Sex Congruent Hand Transforma...mentioning
confidence: 99%
“…Hair follicle can regenerate spontaneously in the center of very large wounds indicate that the potential for HF neogenesis is preserved and can possibly be unleashed by suitable stimuli 5,8,9 . Dermal papilla cells isolated from rat and guinea pig vibrissae, as well as humans, could also induce HF formation when implanted into recipient nonhairy skin 10,11 . Basal keratinocytes also have the capacity to facilitate HF regeneration under induction 12 .…”
mentioning
confidence: 99%
“…DPCs are essential for the hair growth process, 14 playing crucial roles in HF formation during follicular morphogenesis and inducing growth phase (anagen) of the HF cycle. 15,16 The dermal papilla (DP) is widely accepted as the main site of androgen response in the HF for hair growth and hair cycle regulation, [17][18][19] with multiple studies using twodimensionally (2D) cultured primary DPC derived from non-balding and/or balding scalps as models to understand hair growth/loss in AGA. [20][21][22][23] However, 2D cultured DPC inaccurately model cellular conformation of DPC and dermal-epidermal interactions in the HF.…”
Section: Introductionmentioning
confidence: 99%
“…In the hair follicle (HF), dermal papilla cells (DPCs) are present as a tight spherical aggregate in the bulb and are surrounded by epidermal cells such as hair matrix cells, a precursor of specialised keratinocytes. DPCs are essential for the hair growth process, 14 playing crucial roles in HF formation during follicular morphogenesis and inducing growth phase (anagen) of the HF cycle 15,16 . The dermal papilla (DP) is widely accepted as the main site of androgen response in the HF for hair growth and hair cycle regulation, 17–19 with multiple studies using two‐dimensionally (2D) cultured primary DPC derived from non‐balding and/or balding scalps as models to understand hair growth/loss in AGA 20–23 .…”
Section: Introductionmentioning
confidence: 99%